Investigation on the properties of cement-bagasse fiber composite as a structural material - Hamed Nasiry; Ali Varshoei; Abolfazl Kargarfard (تحقیقات علوم چوب و کاغذ ایران, 2011)
In this study the possibility of bagasse fiber usage in Fiber-Cement Composite (FCC) manufacturing, was investigated. Two load of bagasse fiber (%4, 10), three level of calcium chloride as facilitator (5, 7.5 and 10 percent per dry weight of cement) and two type of Portland cement (type II and V) were considered as variables (12 treatments). There were three replicates for each treatment, thus 36 experimental board were manufactured totally. The physical and mechanical properties of experimental specimens were investigated and results analyzed by SPSS software as fully randomized factorial model. As results indicated, there was no significant different between cement type II and V in physical and mechanical properties. The increased loads of calcium chloride caused a striking reduction in mechanical properties and increased water absorption amounts. The best bending strength, modulus of elasticity, IB and minimum thickness swelling were reported in treatment with 4% fibers, 7.5% calcium chloride and type II cement.